A Review On Attitude And Motivation In The English Language Learning For Tahfiz Students In Malaysia - Nur Fattini Mohamad Kamal; Hazlina Abdullah; Haliza Harun (Usuli Faqih Research Centre PLT, 2024)
Al-Qanatir: International Journal of Islamic Studies, Volume 33 Issue 5 Page (162–171)